Streptococcus agalactiae Non-Pilus, Cell Wall-Anchored Proteins: Involvement in Colonization and Pathogenesis and Potential as Vaccine Candidates - Pietrocola, Giampiero; Arciola, Carla Renata; Rindi, Simonetta; Montanaro, Lucio; Speziale, Pietro (Frontiers in Immunology, 2018)
Group B Streptococcus (GBS) remains an important etiological agent of several infectious diseases including neonatal septicaemia, pneumonia, meningitis and orthopaedic device infections. This pathogenicity is due to a varity of virulence factors expressed by Streptococcus agalactiae. Single virulence factors are not sufficient to provoke a streptococcal infection, which is instead promoted by the coordinated activity of several pathogenicity factors. Such determinants, mostly cell wall-associated and secreted proteins, include adhesins that mediate binding of the pathogen to host extracellular matrix/plasma ligands and cell surfaces, proteins that cooperate in the invasion of and survival within host cells and factors that neutralize phagocytosis and/or modulate the immune response. The genome-based approaches and bioinformatics tools and the extensive use of biophysical and biochemical methods and animal model studies have provided a great wealth of information on the molecular structure and function of these virulence factors. In fact, a number of new GBS surface-exposed or secreted proteins have been identified (BibA, LrrG, Srr proteins), the three-dimensional structures of known streptococcal proteins (alpha C protein, C5a peptidase) have been solved and an understanding of the pathogenetic role of “old” and new determinants has been better defined in recent years. Herein, we provide an update of our current understanding of the major surface cell wall-anchored proteins from GBS, with emphasis on their biochemical and structural properties and the pathogenetic roles they may have in the onset and progression of host infection. We also focus on the antigenic profile of these compounds and discuss them as targets for therapeutic intervention.